Effects of light-emitting diodes on the morphology and accumulation of glucosinolates, carotenoids and phenolic acids in red kale sprouts - Bungala, Leonel Tarcisio da Cristina; Sathasivam, Ramaraj; Park, Jong Seok; Kim, Jae Kwang; Park, Sang Un (Journal of Aridland Agriculture, 2024)
Kale (Brassica oleracea var. acephala) has gained popularity as a nutritious and phytochemical-rich vegetable. This study has investigated the effects of three LED treatments (white, blue, and red) on the accumulation of secondary metabolites in kale sprouts. Ten DAS, the kale sprouts were harvested, and growth measurements were measured. Furthermore, selected sprouts were stored at -80 °C for further biochemical analysis, namely, phenolic acids, glucosinolates, and carotenoids. Sprouts irradiated with red LED light showed the best SL, RT, and FW values. For total GSLs, we found that kale sprouts irradiated with white LED lights showed the best results (41.59±0.41 μmol/g DW). Among the aliphatic GSLs, we found that progoitrin presented the best results under blue LED light (17.93±0.49 µmol/g DW), and among the indolic GSLs, glucobrassicin showed the best results under white and red LED light. The highest concentration of total carotenoids was found in kale sprouts under white LED light exposure (3341.27±206.96 μg/g DW). Individually, β-carotene was observed in high concentration under white LED light (1935.13±87.21 μg/g DW). Among the PAs, chlorogenic acid was found in the highest concentration in the treatments under white LED light (45.78±0.73 µg/g DW). In general, kale sprouts irradiated with white LED light showed high contents of GSLs, carotenoids, and PAs. Regarding morphological characteristics, kale sprouts under red LED light showed the most promise. This research offers a valuable approach to enhancing the phytochemicals found in kale sprouting.